2010
DOI: 10.1037/a0017805
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness predicts increased blood pressure: 5-year cross-lagged analyses in middle-aged and older adults.

Abstract: Loneliness is a prevalent social problem with serious physiological and health implications. However, much of the research to date is based on cross-sectional data, including our own earlier finding that loneliness was associated with elevated blood pressure. In this study, we tested the hypothesis that the effect of loneliness accumulates to produce greater increases in SBP over a fouryear period than are observed in less lonely individuals. A population-based sample of 229 50-68 year-old White, Black, and Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
359
4
18

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 562 publications
(423 citation statements)
references
References 57 publications
15
359
4
18
Order By: Relevance
“…• Diminished physical activity 13 • Diminished motor function 14,15 • Symptoms of depression 16 • Disrupted sleep and daytime dysfunction 17 • Impaired mental and cognitive function 18 • Increased systolic blood pressure 19 • Increased sympathetic tone and vascular resistance 20,21 • Increased hypothalamic pituitary adrenocortical activity 22,23 • Altered gene expression related to anti-inflammatory responses 24 • Altered immunity 25,26 Of greater concern, however, is an accumulating volume of research that highlights loneliness as a risk factor for both functional decline as well as increased mortality. 4,8,[27][28][29] In short, there is evidence that the subjective experience of loneliness can significantly contribute to premature death independently of other physical, behavioral, or psychological factors.…”
Section: Effects Of Lonelinessmentioning
confidence: 99%
“…• Diminished physical activity 13 • Diminished motor function 14,15 • Symptoms of depression 16 • Disrupted sleep and daytime dysfunction 17 • Impaired mental and cognitive function 18 • Increased systolic blood pressure 19 • Increased sympathetic tone and vascular resistance 20,21 • Increased hypothalamic pituitary adrenocortical activity 22,23 • Altered gene expression related to anti-inflammatory responses 24 • Altered immunity 25,26 Of greater concern, however, is an accumulating volume of research that highlights loneliness as a risk factor for both functional decline as well as increased mortality. 4,8,[27][28][29] In short, there is evidence that the subjective experience of loneliness can significantly contribute to premature death independently of other physical, behavioral, or psychological factors.…”
Section: Effects Of Lonelinessmentioning
confidence: 99%
“…Studies designed to identify the mechanisms underlying the association between loneliness and mortality have found that loneliness is associated with increased hypothalamic-pituitary-adrenocortical (HPA) activity (Adam et al, 2006;Cacioppo et al, 2006;Doane and Adam, 2010;Glaser et al, 1985;Kiecolt-Glaser et al, 1984;Steptoe et al, 2004), altered gene expression indicative of decreased inflammatory control and increased glucocorticoid insensitivity (Cole et al, 2007(Cole et al, , 2011, increased inflammation, elevated vascular resistance, and blood pressure (Hackett et al, 2012;Hawkley et al, 2006Hawkley et al, , 2010bJaremka et al, 2013), higher rates of metabolic syndrome (Whisman, 2010), diminished immunity (Dixon et al, 2006;Glaser et al, 2005;Kiecolt-Glaser et al, 1984;Pressman et al, 2005;StraitsTröster et al, 1994), increased risk for age-related cognitive decline and dementia (Wilson et al, 2007), and increased sleep fragmentation (Cacioppo et al, 2002;Hawkley et al, 2010a;Jacobs et al, 2006;Kurina et al, 2011). Cross-lagged panel analyses have also shown that loneliness has also been associated with changes in psychological states that can contribute to morbidity and mortality, including increased depressive symptomatology (Booth, 2000;Cacioppo et al, 2006Cacioppo et al, , 2010VanderWeele et al, 2011), lower subjective wellbeing (Kong and You, 2013;VanderWeele et al, 2012), heightened vigilance for social threats (Cacioppo et al, 2015b), and decreased executive functioning (Baumeister and DeWall, 2005;Cacioppo et al, 2000;…”
Section: Introductionmentioning
confidence: 99%
“…Social support can buffer the negative impact of stressful life events on psychological distress, depression, and anxiety as well as alleviate one's loneliness (e.g. [10,14] ). Perceived social support is a "relationship transaction" characterized by the subjective receipt of psychological resources intended to bolster one's ability to cope with stress [9,43] .…”
Section: Gender Differences In Lonelinessmentioning
confidence: 99%